Pembuatan Spot Foto dalam Upaya Peningkatan Destinasi Wisata Desa Tindalun Kabupaten Enrekang - Apriansyah, Muhammad Ansar; Nurfadillah; Syafaruddin; Sari, Junita; Sahrani; Pangestu, Dian Resky; Musmulyadi, Musmulyadi (Makkareso: Riset Pengabdian Masyarakat, 2024)
Indonesia is a country that has extraordinary tourism potential, especially natural tourism. Almost every region in Indonesia has its own characteristics in terms of beauty and natural beauty. Tindalun Village is a village that has quite a lot of natural beauty. However, until now this potential has not been optimized properly. The lack of awareness of the community and village government regarding the importance of tourist destinations in each village means that this potential cannot be utilized optimally. This service activity carries out a work program to create village photo spots so that they can become a tourist attraction. The activity implementation method consists of using 5 stages, namely Village Potential Survey, Work Program Socialization, Joint Discussion, Photo Spot Area Survey, and Photo Spot Creation. The results of the service are photo spots made from materials from the surrounding environment, namely bamboo and areca nut wood.